Conceptual Learning through Accessible Play: Project Torino and Computational Thinking for Blind Children in India - India, Gesu; Ramakrishna, Geetha; Pal, Joyojeet; Manohar, Swami (ICTD 2020, 2020)
Project Torino is a physical programming environment designed for teaching computational thinking to children in schools in the UK, regardless of the level of vision. We introduced project Torino to children in three schools for the blind in Bangalore, India as a toy for playing with songs, rhymes, and stories. We present the results of 103 semi-structured play sessions spread over three months with 12 children (2 girls, 10 boys) with diverse backgrounds. We found that children progressed from playing with pre-connected examples, to making changes, to actively participating in what items are played. Engaging the children in conversation while they played, we established that the teams had grasped three basic concepts of computational thinking–flow of control, variables, and loops without any explicit instructions towards learning them. We propose that play-based approaches can be successfully used with low resource overhead to introduce fundamental concepts of computational thinking.